1993
DOI: 10.1111/j.1600-0560.1993.tb00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the skin: Immunohistochemical and electron microscopic observations

Abstract: A rapidly growing, hemorrhagic, exophytic tumor on the upper back of a 44-year-old male patient was investigated. Histological, immunohistochemical, and electron microscopic studies revealed both basal cell carcinoma-like and spindle cell sarcoma-like structures intermingled in the same tumor. Clinical consequences to this patient were mainly dependent on the sarcomatous element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…In most other cutaneous sarcomatoid carcinomas, however, specific lines of mesenchymal differentiation are not identified and the sarcomatous component resembles atypical fibroxanthoma or high-grade pleomorphic sarcoma. 3,6,14,16,18,19,23,26,33,44 We described some histological findings that have not been reported in the previously published cases of cutaneous sarcomatoid carcinomas. Three of our tumors had predominant malignant giant cell tumor-like tumor components.…”
Section: Discussionmentioning
confidence: 45%
“…In most other cutaneous sarcomatoid carcinomas, however, specific lines of mesenchymal differentiation are not identified and the sarcomatous component resembles atypical fibroxanthoma or high-grade pleomorphic sarcoma. 3,6,14,16,18,19,23,26,33,44 We described some histological findings that have not been reported in the previously published cases of cutaneous sarcomatoid carcinomas. Three of our tumors had predominant malignant giant cell tumor-like tumor components.…”
Section: Discussionmentioning
confidence: 45%
“…The mesenchymal components were multiple, comprising fibrosarcoma, osteosarcoma, chondrosarcoma, and synovial sarcoma, and the patient developed lung metastases 5 years after diagnosis. Izaki et al 18 It is of note that all the cases reported here had nodular BCC as the epithelial components. This low-risk profile may in part explain the apparent low risk for recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 85%
“…1,2,6,[8][9][10] The differing theories range from a collision of 2 synchronous, separate tumors; to the combination of 2 divergent cell lines from a single stem cell; to the conversion from carcinoma to carcinosarcoma by metaplastic transformation of part of the carcinoma in to a sarcoma. 1,2,6,[8][9][10] As most of these cases are associated with a basal cell carcinoma or squamous cell carcinoma 2,[8][9][10][11][12] or, less likely, a malignant adnexal tumor, 2,[8][9][10][11] it may be best to refer to such tumors as ''sarcomatoid carcinoma'' rather than as ''carcinosarcoma,'' as they are likely derived from the epithelial tumor. Malignant cutaneous mixed tumors (myoepithelial carcinomas) may be considered a rare variant of carcinosarcoma, which show true biphasic differentiation, as they appear to be derived from pluripotent stem cells, which give rise to both mesenchymal and epithelial cell types.…”
Section: Discussionmentioning
confidence: 99%